Fortification of coconut oil with sesame oil through micro expeller extraction process - J.M.N. Marikkar (International Coconut Community Journal, 2006)
Value addition to coconut oil is highly desirable in order to increase the range of coconut products. A study was conducted to formulate palatable coconut oil (CNO) blends enriched with essential fatty acid (EFA) using sesame seed as the supplementary source of EFA. For this purpose, micro-expelling process was employed to extract oil blends out of the dried coconut grating mixed with varying proportion of sesame seed (w/w; 0, 1, 2, 3, 4, 5, 7 and 10%). A sensory evaluation by a 30-member semi-trained panel was conducted using a seven-point hedonic scale in order to determine the critical limit of CNO fortification with sesame. Similarly, changes in fatty acid composition were determined using Gas Liquid Chromatography (GLC). Statistical analysis of the sensory data showed that a mild odor of sesame started to appear in the oil blends at 4% level of sesame mixed with dried coconut gratings. According to fatty acid methyl ester (FAME) analysis, the relative increase in linoleic acid was only marginal although there was a substantial increase in unsaturated fatty acid component. At 5% level of fortification, the increment in linoleic acid was 9.2%.